"COMPREHENSIVE ANALYSIS OF LOCKING COMPRESSION PLATE (LCP) TREATMENT FOR PROXIMAL TIBIA FRACTURES: UTILIZING MINIMALLY INVASIVE PERCUTANEOUS PLATE OSTEOSYNTHESIS (MIPPO) TECHNIQUE AND ASSESSING CLINICAL OUTCOMES, COMPLICATIONS, AND FIXATION STRATEGIES" - Dr. Dinesh Kumar Meena; Dr. Raghvendra Choubisa; Dr. Anamendra Sharma; Dr. Ankit Damor (Journal of Population Therapeutics and Clinical Pharmacology, 2021)
This study investigates the application of the locking compression plate (LCP) in conjunction with the minimally invasive percutaneous plate osteosynthesis (MIPPO) technique for the treatment of proximal tibia fractures. Analyzing a cohort of 25 patients, the research explores age distribution, gender, fracture types, plate sizes, fixation principles, and clinical outcomes. Bridging fixation predominates (52%), and excellent/good clinical outcomes are observed in 88% of cases. Complications, including knee joint stiffness and infections, are limited. However, the study acknowledges limitations such as the small sample size. Overall, the findings contribute valuable insights into the efficacy and challenges of LCP and MIPPO in managing proximal tibia fractures.